Caesium tetramethylammonium dodecahydrido-closo-dodecaborate monohydrate - Ioannis Tiritiris; Thomas Schleid (IUCrData, 2016)
In the crystal structure of the hydrated double salt, Cs+·[N(CH3)4]+·[B12H12]2−·H2O, the asymmetric unit contains one caesium and one tetramethylammonium cation, one dodecahydrido-closo-dodecaborate anion and one water molecule. The Cs+ cation is coordinated tetrahedrally by four [B12H12]2− clusters, with the water molecule completing the coordination sphere. The tetramethylammonium cation is surrounded distorted octahedrally by six [B12H12]2− anions. The crystal structure is stabilized by a three-dimensional network of O—H...H—B and C—H...H—B dihydrogen bonds.